Lasers : the new technology of light - Billings, Charlene W. (New York : Facts on File, 1992)
Explains what lasers are and how they work and examines their various uses.
Includes bibliographical references (p. 112-113) and index.
Booklist.
Wilson's Junior High School.
Wilson's Senior High School.
10-12
Young Adult
Keywords: Lasers -- Juvenile literature; Lasers; Lasers